2022
DOI: 10.1111/jocs.16663
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of submitral aneurysm

Abstract: Introduction: Submitral aneurysm is a rare cardiac entity with outpouching in relation to the posterior annulus of the mitral valve. Multiple etiology have been described with the role of infection and inflammation with varied clinical presentation in different case reports. However, the literature on clinical outcome and follow-up is lacking.Material and Method: This retrospective, observational study included all the adult patients (>18 years) who were diagnosed with a submitral aneurysm. Epidemiological, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In their case series on outcomes of submitral aneurysm (SMA), Aggarwal et al provide one of the largest known characterizations and follow-up studies of this infrequently reported pathology. 1 We commend the authors for offering this unique case series and believe it will generate further dialog on the topic. The series details the presentation, etiologies, and outcomes for 10 patients presenting with SMA at a single center.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…In their case series on outcomes of submitral aneurysm (SMA), Aggarwal et al provide one of the largest known characterizations and follow-up studies of this infrequently reported pathology. 1 We commend the authors for offering this unique case series and believe it will generate further dialog on the topic. The series details the presentation, etiologies, and outcomes for 10 patients presenting with SMA at a single center.…”
mentioning
confidence: 98%
“…SMAs are an extremely rare pathology typically found in young patients. [1][2][3] While they were originally described in Western and Southern African populations, SMAs have been identified in patients across a variety of races and ethnicities. 4 In contrast to posterior left ventricular aneurysms, which often occur due to ischemic etiology, SMAs are believed to be largely congenital in nature.…”
mentioning
confidence: 99%
See 3 more Smart Citations